Effect of Extending Corticotomy Depth to Trabecular Bone on Accelerating Orthodontic Tooth Movement in Rats - Thanapat Pathomkulmai; Pannapat Chanmanee; Bancha Samruajbenjakun (MDPI AG, 2022)
Corticotomy is a surgical procedure that induces injury to the cortical bone to accelerate tooth movement. This study aimed to increase the depth of corticotomy to the trabecular bone and to evaluate the amount and rate of tooth movement and alveolar bone changes in response to various degrees of cortical and trabecular bone injury. Seventy-eight male Wistar rats were randomly divided into four groups based on procedure used: (1) baseline control group of orthodontic tooth movement (OTM) only; (2) OTM + 4 corticotomies (CO); (3) OTM + 4 osteotomies (OS); and (4) OTM + 16 CO. A closed-coil nickel-titanium spring was placed to move the maxillary first molar mesially with a 10 g force. On days 0, 7, 14, and 21, alveolar bone alteration and tooth movement were measured using microcomputed tomography. Significant tooth movement was related to the number and the depth of the perforations. The OTM + 16 CO group showed a greater amount and rate of tooth movement than the OTM + 4 CO group. When osteotomy and corticotomy were compared with the same volume of bone removed, the OTM + 4 OS group had a faster rate of tooth movement than the OTM + 16 CO group during the first week, with significantly reduced bone volume. However, no significant difference was observed in the amount of tooth movement between the OTM + 4 OS and OTM + 16 CO groups at the end of the study. Extending the depth of corticotomy to trabecular bone increased the amount of tooth movement by accelerating the induction and completion of bone remodeling, which accelerated the rate of tooth movement during the initial stage.